The Role of Knowledge Management and Cause Related Marketing towards Sustainability to promote Societal Marketing Concept - Qadeer, Rooma; Rafi, Nosheen (Pakistan Journal of Humanities and Social Sciences, 2025)
This study aims to categorize and validate the histories and results of environmental sustainability in green manufacturing in Pakistan, with a primary focus on small and medium-sized businesses (SMEs). This study investigates how knowledge management processes (KMPs), more especially knowledge application, dissemination, and acquisition, function as precursors to environmental sustainability. Partial least squares structural equation modeling (PLS-SEM) was used to examine data gathered from 450 SMEs via an online survey. This study investigates how, in the context of green manufacturing, CRM, knowledge management, and environmental sustainability are related. Important results show that: (1) CRM significantly affects environmental sustainability, and (2) CRM moderates the eco-friendly relationship between KM and environmental sustainability. The study's conclusions have significant ramifications for researchers, managers, and policymakers who want to comprehend the dynamics of environmental sustainability in Pakistani SMEs engaged in green manufacturing. Limitations and future research directions are also covered in this work.